1992
DOI: 10.1269/jrr.33.342
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Incidence among Atomic Bomb Survivors, 1950-80.

Abstract: Colorectal cancer incidence in the LSS sample during 1950-80 was investigated. A total of 730 incidence cases of colorectal cancer were confirmed from a variety of sources. Sixty-two percent of the cancers were microscopically verified and 12% were ascertained through death certificate only. The risk of colon cancer increased significantly with intestinal dose, but no definite increase of risk was observed for rectal cancer. Relative risk at 1 Sv and excess risk per 10(4) PY-Sv for colon cancer are 1.80 (90% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…Strong evidence has been found for a relationship between ionizing radiation exposure and colon cancer risk, although evidence for rectal cancer has been inconsistent . Among atomic bomb survivors, the colon cancer rates increased with radiation dose in studies of incidence and mortality, while there was no evidence of radiation effects on rectal cancer rates . Nakatsuka et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strong evidence has been found for a relationship between ionizing radiation exposure and colon cancer risk, although evidence for rectal cancer has been inconsistent . Among atomic bomb survivors, the colon cancer rates increased with radiation dose in studies of incidence and mortality, while there was no evidence of radiation effects on rectal cancer rates . Nakatsuka et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nakatsuka et al . reported that all colon subsites (cecum and ascending, transverse and descending and sigmoid colon) were equally sensitive to radiation among atomic bomb survivors followed through 1980, whereas rectum was not …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both radiation exposure and metabolic/hormonal dysregulation have been linked to altered intestinal homeostasis and colorectal carcinogenesis252728293031323334. Epidemiological observations linking radiation and colorectal cancer (CRC) are also well supported by studies in animal models43536.…”
mentioning
confidence: 99%